Cabozantinib is selectively cytotoxic in acute myeloid leukemia cells with FLT3-internal tandem duplication (FLT3-ITD). Issue 2 (1st July 2016) - Lu, Jeng-Wei; Wang, An-Ni; Liao, Heng-An; Chen, Chien-Yuan; Hou, Hsin-An; Hu, Chung-Yi; Tien, Hwei-Fan; Ou, Da-Liang; Lin, Liang-In
Highlights: Cabozantinib, an oral multikinase inhibitor, was cytotoxic to myeloid leukemia cells with FLT3 -ITD in vitro and in vivo . Cabozantinib induced MV4-11 cell cycle arrest and apoptosis. Cabozantinib significantly inhibited MV4-11 and Molm-13 tumor growth at a dosage of 10 mg/kg and showed longer survival rate. Abstract: Cabozantinib is an oral multikinase inhibitor that exhibits anti-tumor activity in several cancers. We found that cabozantinib was significantly cytotoxic to MV4-11 and Molm-13 cells that harbored FLT3 -ITD, resulting in IC50 values of 2.4 nM and 2.0 nM, respectively. However, K562, OCI-AML3 and THP-1 (leukemia cell lines lacking FLT3 -ITD) were resistant to cabozantinib, showing IC50 values in the micromolar range. Cabozantinib arrested MV4-11 cell growth at the G0 /G1 phase within 24 h, which was associated with decreased phosphorylation of FLT3, STAT5, AKT and ERK. Additionally, cabozantinib induced MV4-11 cell apoptosis in a dose-dependent manner (as indicated by annexin V staining and high levels of cleaved caspase 3 and PARP-1), down-regulated the anti-apoptotic protein survivin and up-regulated the pro-apoptotic protein Bak. Thus, cabozantinib is selectively cytotoxic to leukemia cells with FLT3 -ITD, causing cell-cycle arrest and apoptosis. In mouse xenograft model, cabozantinib significantly inhibited MV4-11 and Molm-13 tumor growth at a dosage of 10 mg/kg and showed longer survival rate. Clinical trials evaluating the efficacy of cabozantinib in acute myeloid leukemia (AML) with FLT3 -ITD are warranted.